Survei Tingkat Kecepatan dan Kelincahan Pemain Sekolah Sepak Bola - Reyzqi Pitoyo, Muhammad; Imansyah, Farizal; Rizhardi, Rury (INNOVATIVE SCIENCE AND TECHNOLOGY LEARNING JOURNAL, 2026)
The problem in this research is that the level of speed and agility of the SSB Putera Sukma Palembang players is not yet known. The purpose of this study was to determine the level of speed and agility of the SSB Putera Sukma Palembang players. The method used in this study used a survey method with data collection techniques using tests and measurements. This type of research is a quantitative descriptive study. The data analysis technique used descriptive statistics, the percentage of P (percentage) = F (frequency) / N (number of respondents) X 100%. The population in this study amounted to 34 players of SSB Putera Sukma Palembang. The sample in this study amounted to 26 players SSB Putera Sukma Palembang who were selected by purposive sample with certain criteria. The instrument used is a 30 meter run to measure speed, while the Illinois race is used for speed. Based on the research results, the speed level of SSB Putera Sukma Palembang players is in the good category (43.61%) and for the speed is in the medium category (80.76%).